Management of Visceral Artery Pseudoaneurysms by Combined Technique of Percutaneous Thrombin Injection and Endovascular Coiling - Kalpana Sivalingam; Karthik Palanisamy; Amalan Ignatius (Journal of Clinical Interventional Radiology ISVIR)
Purpose To describe our initial experience with percutaneous thrombin injection combined with endovascular coiling of high-flow visceral artery pseudoaneurysms. Materials and Methods Institutional review board approval was obtained. Between January 2019 and February 2020, 21 patients with nonvariceal upper gastrointestinal (GI) bleed underwent multidetector CT angiography. Four patients with acute pancreatitis and large pseudoaneurysms were selected for the combined technique. Human thrombin reconstituted with calcium chloride was injected percutaneously. Partially thrombosed aneurysms were treated up to three times. Simultaneously or within 15 days, coil embolization of the neck or patent part of pseudoaneurysm was performed. Patients were followed up to 1 month postprocedure. Results The size of the pseudoaneurysms ranged from 3 cm to 6 cm. All were accessed percutaneously by 22G Chiba needle under ultrasound guidance and 500 to 1500 units of thrombin was injected in one to three attempts. Subsequently, endovascular coiling of the neck of the pseudoaneurysm or of the feeding artery was performed. Technical success with cessation of flow was achieved in all four patients. One patient developed obstructive jaundice postprocedure and another continued to have GI bleeding despite thrombin injection. Conclusion Percutaneous thrombin injection is an easy to use and effective tool for treating visceral artery pseudoaneurysms and can be combined with endovascular coiling for successful occlusion of large pseudoaneurysms.